2021
DOI: 10.1111/bjso.12477
|View full text |Cite
|
Sign up to set email alerts
|

Seeking and avoiding contact with Muslims at a Hijab Stall: Evidence for multilayer, multi‐determined solidarity, courage, apathy, and moral outrage

Abstract: Intergroup contact is key to social cohesion, yet psychological barriers block engagement with diversity even when contact opportunities are abundant. We lack an advanced understanding of contact seeking because intergroup contact is often an independent variable in research, and studies on contact seeking have favoured experimental probing of selected factors or measured only broad behavioural intentions. This research carried out the first ecological tests of a novel multilayer-multivariate framework to cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(16 citation statements)
references
References 104 publications
1
15
0
Order By: Relevance
“…Our work takes a different approach, examining how the roles that people occupy (in this case, mothering) shape the ways in which they use a public space and hence afford or constrain opportunities for contact. Furthermore, we found that despite the playgrounds’ nature as semipublic spaces where visitors are meant to socialize with each other, their actual use often involved premeditated meetings with existing friends, offering the mothers relaxed peer contact for the relatively brief time spent on the playground (see Al Ramiah et al 2015; Paolini et al 2022). Thus, our results support previous research findings that outgroup avoidance derives not only from intergroup processes but also from personal preferences or passivity (Mackinnon et al 2011; Paolini et al 2022).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our work takes a different approach, examining how the roles that people occupy (in this case, mothering) shape the ways in which they use a public space and hence afford or constrain opportunities for contact. Furthermore, we found that despite the playgrounds’ nature as semipublic spaces where visitors are meant to socialize with each other, their actual use often involved premeditated meetings with existing friends, offering the mothers relaxed peer contact for the relatively brief time spent on the playground (see Al Ramiah et al 2015; Paolini et al 2022). Thus, our results support previous research findings that outgroup avoidance derives not only from intergroup processes but also from personal preferences or passivity (Mackinnon et al 2011; Paolini et al 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Ingroup company is also preferred because it consumes less resources than intergroup interaction (Al Ramiah et al 2015). Therefore, outgroup avoidance can result from apathy rather than hostility (Paolini et al 2022).…”
Section: Informal Segregation Built Into Practices and Ingrained In C...mentioning
confidence: 99%
“…However, the contact-seeking literature has neglected mediated contact. Following Paolini et al's (2021) strategy, we adopt a multi-layer-multivariate framework by examining clusters of variables at the intrapersonal (e.g., personality), interpersonal (e.g., need for uniqueness), interactional (e.g., past intercultural contact experiences), and intergroup (e.g., diversity attitudes) levels. We organize our predictors into three categories of variables likely to predict approaching outgroup media: personality, attitudinal, and past contact experiences.…”
Section: What Predicts Approaching the Outgroup?mentioning
confidence: 99%
“…Such patterns are clear in the interpersonal contact literature (e.g., Paolini et al, 2021), but have not been examined with media contact. We also predict that past intergroup experiences will influence outgroup media exposure choices.…”
Section: What Predicts Approaching the Outgroup?mentioning
confidence: 99%
See 1 more Smart Citation